IMPLEMENTASI UNDANG-UNDANG NOMOR 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN DI KANTOR KECAMATAN GANTAR, INDRAMAYU - Rahim, Abdur; Zahwa Al Alif, Muamar; Nur, Hafiz An; Syadid, Ahmad Qaulan; Al Salma, Ariny Nur (Gapenas Publisher, 2025)
This study aims to analyze the implementation of Law Number 30 of 2014 on Government Administration at the Gantar Subdistrict Office, Indramayu Regency. The research employed a qualitative approach with a case study method. Data were collected through in-depth interviews, field observations, and document analysis. The findings reveal that the implementation of the law has not yet been fully optimized due to limitations in human resources, insufficient regulatory training, and a lack of policy socialization. Nevertheless, the subdistrict office has made efforts to improve service quality by applying the principles of good governance and introducing digital-based services.